Phytochemical screening of a therapeutic plant mussaenda luteola delile (rubiaceae) - T, Betty; P, Sumathi; T, Indhumathi; B, Prabavathi; B, Devadharshini (Kongunadu Research Journal, 2020)
The contribution of angiosperms to the biodiversity is extremely important since human life totally depends on it. They are of rich in secondary metabolites, vitamins and their derivatives. Mussaenda luteola Delile. is one such angiospermic plant in the family Rubiaceae. The present study emphasis on the preliminary phytochemical analysis of the leaf extracts of M. luteola under various solvent systems viz.,petroleum ether, chloroform, ethanol and aqueous. The study validates the presence of steroids, triterpenoids, quinone, alkaloids, flavonoids, phenols, coumarines, glycosides, tannins in all the four solvent systems. The leaves of M. luteola were further investigated for their total flavonoid and steroid content and this plant records decent phenol content under studies. This reveals that the leaves have potential to serve in pharmaceutical industries as significant candidature. Since the leaf part of this plant shows the occurrence of various phytochemicals it could serve as an alternate drug in pharmaceutical industries and as an ideal model for the production and development of new novel herbal drugs as well as in the field of broad spectrum of research